Determinants of HIV-1 reservoir size and long-term dynamics during suppressive ART - Nadine Bachmann (Nature Portfolio, 2019)
Here, Bachmann et al. provide data on long-term dynamics of the HIV-1 reservoir in 1,057 individuals on suppressive antiretroviral therapy and show that in 26.6% of individuals the reservoir increases. Viral blips and low-level viremia are significantly associated with a slower reservoir decay.